Inuktun an introduction to the language of Qaanaaq, Thule - Fortescue, Michael D. 1946- (1991)
This study of the dialect (Polar Eskimo, Thulesproget, Inuktun or Avanersuarmiutut) spoken by the Inughuit, the Inuit hunters living in the northwest tip of Greenland near Thule, focusses on the speech of the groups aged 30-50, who are least affected by West Greenlandic and Danish speech. Settlements included are Qaanaaq, Havighivik, Muriuhaq, Qikiqtat, Qikiqtarhuaq and Hiurapaluk. The study includes a thematic dictionary and sample text.
Keywords: Inuktitut (Langue) - Dialectes - Groenland; Grammatik; Inuit language -- Glossaries, vocabularies, etc; Inuit language -- Grammar; Polar Eskimos; Polareskimoisch